# Divide the polynomial $p(x)$ by the polynomial $g(x)$ and find the quotient and remainder, in each of the following:(i) $p(x) = x^3 - 3x^2 + 5x -3, g(x) = x^2-2$(ii) $p(x) =x^4 - 3x^2 + 4x + 5, g(x) = x^2 + 1 -x$(iii) $p(x) = x^4 - 5x + 6, g(x) = 2 -x^2$

#### Complete Python Prime Pack for 2023

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack 2023

8 Courses     2 eBooks

To do:

We have to divide the polynomial $p( x)$ by the polynomial $g( x)$ and find the quotient and remainder in each case.

Solution:

(i) As given, $( p(x)=x^{3}-3 x^{2}+5 x-3$, $g(x)=x^{2}-2$

On Dividing $p( x)$ by $g( x)$ by long division:

$x^2-2$)$x^3-3x^2+5x-3$($x-3$

$x^3-2x$

---------------------

$-3x^2+7x-3$

$-3x^2+6$

--------------------

$7x-9$

Quotient$=x-3$

Remainder$=7x-9$.

(ii) $p(x) = x^4 - 3x^2 + 4x + 5$

$g(x) = x^2+1 -x$

$x^2-x+1$)$x^4-3x^2+4x+5$($x^2+x-3$

$x^4+x^2-x^3$

-------------------------

$x^3-4x^2+4x+5$

$x^3-x^2+x$

---------------------------

$-3x^2+3x+5$

$-3x^2+3x-3$

----------------------

$8$

---------

Therefore, the quotient is $x^2+x-3$ and the remainder is $8$.

(iii) $p(x) = x^4 - 5x + 6$

$g(x) = 2 -x^2$

$2-x^2$)$x^4-5x+6$($-x^2-2$

$x^4-2x^2$

------------------

$2x^2-5x+6$

$2x^2-4$

--------------------

$-5x+10$

Therefore, the quotient is $-x^2-2$ and the remainder is $-5x+10$.

Updated on 10-Oct-2022 13:19:34